Shakespeare and Mercy at the Vatican, 2016 - Cerezo Moreno, Marta (International Journal of English Studies, 2020)
This article explores a central chapter in the history of the Catholic reception of Shakespeare’s work during the contemporary age: the Catholic readings in 2016 of Shakespeare’s dramatic presentation of mercy in the context of the celebrations of the 400th anniversary of Shakespeare’s death and the Holy Year of Mercy. This study directs its focus first to Catholic public manifestations on mercy −such as printed volumes, articles and cycles of lectures− which incorporated Shakespeare’s reflections on mercy within their religious debate. Second, it studies how the Globe to Globe Hamlet performance at the Holy See on 13 April 2016 triggered the interpretation within the Vatican context of Hamlet as a play which, despite its focus on revenge and crime, opens up glimpses of mercy that allow a redefinition of justice.